2020
DOI: 10.1155/2020/4636271
|View full text |Cite
|
Sign up to set email alerts
|

Fighting Left Handers Promotes Different Visual Perceptual Strategies than Right Handers: The Study of Eye Movements of Foil Fencers in Attack and Defence

Abstract: Left handers have long held the edge over right handers in one-on-one interactive combat sports. Particularly in fencing, top rankings show a relatively strong overrepresentation of left handers over right handers. Whether this can be attributed to perceptual strategies used by fencers in their bouts remains to be established. This study aims to verify whether right-handed fencers assess their opponents’ behaviour based on different perceptual strategies when fencing a left vs. right hander. Twelve top-level (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 38 publications
0
15
1
Order By: Relevance
“…They might not have been trained to form a mature cognitive process, from using advanced cues and information, as well as receiving signals and stimuli, to making the right response. All of this results in a low efficiency of their visual search strategy, with unclear purpose of their intentional fixations (Yan, 2015;Witkowski et al, 2018Witkowski et al, , 2020. Based on our findings, the type of stimulus material used may affect the differences between experts and non-experts for the various behavioral measures investigated.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…They might not have been trained to form a mature cognitive process, from using advanced cues and information, as well as receiving signals and stimuli, to making the right response. All of this results in a low efficiency of their visual search strategy, with unclear purpose of their intentional fixations (Yan, 2015;Witkowski et al, 2018Witkowski et al, , 2020. Based on our findings, the type of stimulus material used may affect the differences between experts and non-experts for the various behavioral measures investigated.…”
Section: Discussionmentioning
confidence: 66%
“…They might not have been trained to form a mature cognitive process, from using advanced cues and information, as well as receiving signals and stimuli, to making the right response. All of this results in a low efficiency of their visual search strategy, with unclear purpose of their intentional fixations (Yan, 2015 ; Witkowski et al, 2018 , 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Participants with less expertise spent significantly less time directing gaze to the mini-trampoline during the MTVT task compared to the MT skill (see Table 1 ). A meta-analysis [ 17 ] reported that gaze behaviour is indeed moderated by task complexity, and several published reports have corroborated the malleability of visual regulation using other related tasks [ 17 , 28 , 29 , 30 , 31 ]. The emergence of different visual behaviours depends on task characteristics and complexity, although the more-expert group demonstrated similar gaze behaviours when performing on MT and MTVT.…”
Section: Discussionmentioning
confidence: 99%
“…In taekwondo-as in other combat sports-it is important to take into consideration stimulus-response in order to anticipate the opponent's actions and act accordingly to win the bout [43][44][45], specifically by behaving creatively to surprise the opponent [11]. Specifically, winners scored one point with direct attacks to the chest.…”
Section: Discussionmentioning
confidence: 99%